Analisis Penggunaan Variasi Bahasa Sakai dan Bahasa Melayu di Kabupaten Bengkalis Provinsi Riau - Rian Azmul Fauzi; Siswanto Siswanto; Deni Afriadi (Departement of Mathematics Education, 2024)
This article is intended to look further at the use of dialect variations in Sakai and Malay in Bengkalis Regency, Riau Province. Use phoneme variations on each word used to convey something. In addition, this study also tries to describe the forms of retention from native Malay to Sakai. This study uses a qualitative method, with analyzing research data using the matching method and comparative linking techniques to obtain appropriate and valid research data. The technique used is to find variations in Malay and Sakai in the form of one variant, both in the form of the meaning of an utterance and into another form. After that, make a comparative study between the two variations of the language used. So it appears several differences in the use of language used by each speaker. In this study the authors found various forms of dialect variation in Sakai language and Malay that are used by a group of people in conducting social interaction when expressing their intended purposes and objectives. In addition to the many forms of language variation used, there are also phoneme variations in each utterance spoken, including phonemes [/ħ/, /ñ/, /η/, /∂/, /ε/, /ə/, /?/] and other phonemes. This gives rise to the retention form of the original Malay language that is used by the Sakai language community in several meanings of utterance. In this study, using descriptive qualitative research methods with analyzing data using the matching method and comparative relationship techniques in order to obtain valid research data. The use of variations of Malay and Sakai dialects in this study is also presented comprehensively and completely.